Biomass Fuel Use and Respiratory Health Among Ga-Kenkey makers At Chorkor, A Suburb of Accra in the Greater Accra Region, Ghana - Twum, B.Y. (University of Ghana, 2017)
Background: The use of biomass fuel for cooking leads to the production of air pollutants which could be deleterious to human health. Some studies have reported decreased pulmonary function and prevalence of certain respiratory symptoms among biomass fuel users. However, no study has been conducted to investigate the relationship between Ga-kenkey making, an activity heavily reliant on use of biomass fuel and respiratory health of Ga-kenkey makers. Objective: The primary objective of this study was to assess the relationship between biomass fuel use and respiratory health among Ga-kenkey makers in Accra. Methods: A cross-sectional analytical study was conducted from May to July, 2017 among 52 purposively selected Ga-kenkey makers at Chorkor, a suburb of Accra. Semi-structured questionnaire and spirometry were used to collect data from study participants. Mean values and standard deviations of participants, cross tabulations and Chi-square analysis were computed to find relationship between hours spent using biomass fuel and pulmonary symptoms. The associations between duration of work and pulmonary indices were assessed using multivariate linear regression analysis. Statistical analysis was done in STATA software version 14. ResaID: The mean age±SD of Ga-kenkey makers was 41.87± 11.11 years. The most commonly selfreported respiratory symptoms included itchy and watery eyes, 40 (76.92%); itchy ears and throat, 32 (61.54%); prolonged or repeated sneezing 30 (57.69%) and colds, 29 (55.77%). The study recorded reduced pulmonary indices. The mean±SD pulmonary indices were FVC (2.45L±0.58L); FEV) (1.65US%0.48Us) and FVCIFEVI (68.12s·1 ±14.09 S·I). There was no significant association between the duration of work and the pulmonary indices. Conclusion: In conclusion, this study demonstrated no significant statistical relationship between duration of work as a Ga-kenkey maker and lung function parameters among the study participants.
MPH
Keywords: Biomass Fuel; Respiratory Health; Ga-Kenkey makers; Chorkor; Ghana; Spirometry; Respiratory symptoms; Pulmonary function